2005
DOI: 10.1080/02688690500080893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on cognition and apathy in normal pressure hydrocephalus: A case study and review

Abstract: The psychostimulant methylphenidate has been previously shown to improve cognitive performance in both normal control volunteers and patient populations. In the present case study, the effects of methylphenidate on cognitive and behavioural function were examined in a single patient with idiopathic normal pressure hydrocephalus (NPH) who had undergone ventriculoperitoneal shunting. A double-blind placebo-controlled ABBA drug design was employed, with the administration of two different doses of methylphenidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…All of the trials were small (between 1 and 70 participants) and compared methyphenidate with placebo. Seven trials, 20, 22, 24, 27, 29, 30, 32 including two “N-of-1” trials,27, 29 were crossover trials and six21, 23, 25, 26, 28, 31 were parallel comparisons. Most of the trials provide limited methodologic details, limiting our ability to assess the validity of the individual trials.…”
Section: Resultsmentioning
confidence: 99%
“…All of the trials were small (between 1 and 70 participants) and compared methyphenidate with placebo. Seven trials, 20, 22, 24, 27, 29, 30, 32 including two “N-of-1” trials,27, 29 were crossover trials and six21, 23, 25, 26, 28, 31 were parallel comparisons. Most of the trials provide limited methodologic details, limiting our ability to assess the validity of the individual trials.…”
Section: Resultsmentioning
confidence: 99%
“…Unusual appearances of NPH symptoms may hinder early diagnosis and consequently proper treatment 5,6,7 . Sometimes, even response to typical treatment in psychiatric syndromes may be impaired, like a described patient having schizophrenia with intolerance to even low dose of antipsychotics, who was subsequently revealed to be having communicating normal pressure hydrocephalus 19,20 . We did not evaluate a control group without NPH in order to compare our findings in idiopathic NPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…That study found a significant improvement in AES scores after 12 weeks of treatment. Other case reports have described using MTP to effectively treat apathy in the depressed population [135,136], the Parkinson's population [131], cerebrovascular accident patients [139], and patients with idiopathic normal pressure hydrocephalus [133]. Another recent RCT reported that apathy scores improved significantly in depressed patients who were treated with MTP in combination with an antidepressant, compared to patients using the antidepressant alone [138].…”
Section: Pharmacotherapy (Table 2)mentioning
confidence: 99%